Desarrollo de un modelo de control de inventario para optimizar la gestión operativa en la empresa calzado el marino en el cantón el empalme - Arias Cruz, Diana Lissbeth (2024)
The current research work is about “Development of an inventory control model to optimize operational management in the company CALZADO EL MARINO in the canton of El Empalme”. The main objective is to propose a specific inventory control model for the company that significantly improves operational efficiency. To achieve this result, a survey was carried out with the owner to understand in detail the current situation of the company. For the development of this research, a process mapping was carried out from the moment the order is placed until the order arrives, in order to find critical points in the logistics process. Once the problem facing the company was identified, the inventory model proposal was developed. After detailed analysis, a software called basic point of sale was chosen. This software offers tools that allow detailed inventory control. Finally, a detailed analysis of the costs linked to the implementation of the inventory was carried out. In this analysis, a detailed calculation was made and the Microsoft Excel tool was used to obtain the most precise and reliable results. This allowed us to have a clearer vision of whether inventory software is recommended or not when evaluating costs.